2022
DOI: 10.3389/fphar.2022.967623
|View full text |Cite
|
Sign up to set email alerts
|

Chaihu Shugan powder alleviates liver inflammation and hepatic steatosis in NAFLD mice: A network pharmacology study and in vivo experimental validation

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is the most common metabolic disease and is intertwined with cardiovascular disorders and diabetes. Chaihu Shugan powder (CSP) is a traditional Chinese medicine with a significant therapeutic effect on metabolic diseases, such as NAFLD. However, its pharmacological mechanisms remain to be elucidated.Methods: The main compounds of CSP were measured using LC-MS/MS. A network pharmacology study was conducted on CSP. Its potential active ingredients were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For example, Qiang Zhang et al found that the active metabolite of Radix Bupleuri, β-sitosterol, reduced lipid accretion in hepatocytes processing free aliphatic acids by activating the PPARγ-UCP-1 pathway, thus exerting anti-hepatic fibrosis effects ( Zhang Y. et al, 2022 ). Lei et al (2022) found that the traditional Chinese medicine formula Chaihu Shugan powder (containing Radix Bupleuri as the main metabolite) ameliorated lipid accretion in the livers of mice with non-alcoholic fatty liver disease, inhibited secretion of inflammatory cytokines in hepatic tissues, and inhibited synthesis of aliphatic acids in the liver. The active metabolite of Salvia miltiorrhiza, cryptotanshinone, activates the AMPK signaling pathway, inhibits fat formation, aliphatic acid oxidation, oxidative stress, and inflammatory reactions, thus ameliorating ethanol-induced liver damage ( Nagappan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Qiang Zhang et al found that the active metabolite of Radix Bupleuri, β-sitosterol, reduced lipid accretion in hepatocytes processing free aliphatic acids by activating the PPARγ-UCP-1 pathway, thus exerting anti-hepatic fibrosis effects ( Zhang Y. et al, 2022 ). Lei et al (2022) found that the traditional Chinese medicine formula Chaihu Shugan powder (containing Radix Bupleuri as the main metabolite) ameliorated lipid accretion in the livers of mice with non-alcoholic fatty liver disease, inhibited secretion of inflammatory cytokines in hepatic tissues, and inhibited synthesis of aliphatic acids in the liver. The active metabolite of Salvia miltiorrhiza, cryptotanshinone, activates the AMPK signaling pathway, inhibits fat formation, aliphatic acid oxidation, oxidative stress, and inflammatory reactions, thus ameliorating ethanol-induced liver damage ( Nagappan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chaihu Shugan powder (CSP) is a Chinese medicine that is used to dredge the liver and regulate Qi, energize blood, and reduce pain ( 85 ), and it is a general remedy for NAFLD. CSP is composed of Radix Bupleuri, Citrus Reticulata , Chuanxiong Rhizoma, Paeoniae Radix Alba, Aurantii Fructus, Cyperi Rhizoma and Radix Glycyrrhizae.…”
Section: Tcm and Monomers Regulates Ferroptosis To Inhibit Nonalcohol...mentioning
confidence: 99%
“…Chaihu Shugan powder (CSP) is a Chinese medicine that is used to dredge the liver and regulate Qi, energize blood, and reduce pain (85), and it is a general remedy for NAFLD. CSP is composed of Radix…”
Section: Chaihu Shugan Powdermentioning
confidence: 99%
“…Chaihu Shugan significantly reduced the rate of CGS recurrence compared with the placebo, with minimal adverse effects. Furthermore, Chaihu Shugan has been used to treat a variety of metabolic gastroenterological and hepatobiliary conditions, including chronic gastritis ( Qin et al, 2013 ), irritable bowel syndrome ( Hang et al, 2022 ), hepatic injury ( Jia et al, 2017 ), liver inflammation and hepatic steatosis ( Lei et al, 2022 ), and non-alcoholic fatty liver disease (NAFLD) ( Wang et al, 2022a ). Scientists have hypothesized that the therapeutic effects of Chaihu Shugan are attributed to its ability to modulate gut microbiota dysbiosis and improve metabolic disorders ( Liang et al, 2018 ; Yang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%